Intracellular changes of Na+, K+, Ca++ & Mg++ in rat pancreatic islets in different glucose concentration and their relation with insulin secretion (Journal of Dhaka National Medical College & Hospital, 2013)
Impairment of insulin secretion from pancreatic ?cell constitutes an important pathophysiological factor in the development of diabetes mellitus. The changes of intracellular concentration of Na+, K+, Ca++ and Mg++ were observed in substimulatory and stimulatory different glucose concentrations. Pancreatic islets from Long-Evans rats were isolated by collagenase digestion. The concentrations of ions expressed in terms of islet protein in the homogenized islets were measured by using an ion-sensitive electrode based autoanalyzer. In the physiological medium, the islet content of all the four ions increased significantly in response to glucose with maximum level at 11 mM and no further increase at 20 mM. Initial depolarizing effect of glucose is due to reduction of K+ permeability. The reduction of K+ permeability by glucose in ?cell is a major step in stimulus-secretion coupling for insulin release. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16016 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 17-20